12-2X+3X=-3-2

Simple and best practice solution for 12-2X+3X=-3-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-2X+3X=-3-2 equation:


Simplifying
12 + -2X + 3X = -3 + -2

Combine like terms: -2X + 3X = 1X
12 + 1X = -3 + -2

Combine like terms: -3 + -2 = -5
12 + 1X = -5

Solving
12 + 1X = -5

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 1X = -5 + -12

Combine like terms: 12 + -12 = 0
0 + 1X = -5 + -12
1X = -5 + -12

Combine like terms: -5 + -12 = -17
1X = -17

Divide each side by '1'.
X = -17

Simplifying
X = -17

See similar equations:

| -2=1+C | | spx-7=2px+2 | | 2=B-6 | | 4927=n/15 | | .6666y+4=2x | | 3=-11+A | | m-9m-m+9= | | y-36=-28 | | 5/x+8/3x^2 | | 3xy+3yx= | | mx+25=-36 | | f=73905/15 | | 3xy=3yx | | m+7m-3m+4= | | X^2-8=3 | | 73905=n/15 | | V=3.14R2h/3 | | -3/2(1) | | -2-2w+2=2-7w+2 | | m-2m-8m+7= | | 0=-2x^2+6x | | (2xy)(5xy)= | | 5x+85-53/2x=51 | | 32x^2+12x+1= | | 12y^2(y/3+9x/y2)=4y^3-72 | | 4z-3(z+1)=2(z-3)-z | | 11/6/(-8) | | 49x^2-14x-48= | | -21x^2-31x-8= | | 13=-7x-8 | | -8(x+2)=24 | | 16x^2+34x+15= |

Equations solver categories